Efficient and stable photocatalytic H2 evolution by self-assembly of zirconium(iv) coordination with perylene diimide supramolecules under visible light irradiation. Issue 12 (2nd March 2021) - Ding, Haoran; Wang, Zhiqiang; Kong, Kangyi; Feng, Shufan; Xu, Lifeng; Ye, Haonan; Wu, Wenjun; Gong, Xueqing; Hua, Jianli
Abstract : Self-assembly of Zr IV coordination with PDI supramolecules can facilitate separation and transfer of charge carriers. The photocatalyst P-PMPDI-Zr (1 : 0.25) achieved a superior HER activity of 50.46 mmol g −1 h −1 with an AQY of 11.7% at 630 nm. Abstract : Wide spectral response and rapid separation and transfer of charge carriers are critical to the high activity of photocatalysts. Metal ions can work as an electron mediator to promote charge transfer. Therefore, we adopted the strategy of forming coordination bonds between metal cations of zirconium(iv ) with a perylene diimide (PDI)-based organic supramolecular system to broaden the absorption spectrum and facilitate separation of photoinduced charges. We successfully prepared a series of doped supramolecular photocatalysts P-PMPDI containing different contents of Zr IV cations via phosphonate/Zr IV coordination bonds, and among them, P-PMPDI-Zr (Zr IV  : P-PMPDI = 0.25 : 1) exhibited the highest activity toward the hydrogen evolution reaction (HER) of 2.52 mmol h −1 (50.46 mmol g −1 h −1 ) with an apparent quantum yield of 11.7% at 630 nm and good stability. Besides, we also prepared Co, Ni, and Cu-doped P-PMPDI supramolecular catalysts (M : P-PMPDI = 0.25 : 1), all of which showed higher HER activity than the bare P-PMPDI, but still lower activity than P-PMPDI-Zr . X-ray photoelectron spectroscopy (XPS), electron spin resonance (ESR) and density functional theory (DFT) calculations further demonstrated that Zr III ions formed in the photocatalytic process are the active sites, rendering the supramolecular photocatalyst P-PMPDI-Zr more favorable for photocatalytic H2 evolution.